SLPI as a dedifferentiation biomarker in BRAFV600E-mutant papillary thyroid cancer - Wei Luo; Xin Ji; Xiang-Yu Tan; Yu-Ting Li; Zhi-Qiang Zhang; Chui-Mian Zeng (Endocrine Connections)
The BRAFV600E mutation drives papillary thyroid carcinoma (PTC) progression and therapy resistance, yet its downstream effectors remain incompletely characterized. Here, we identify secretory leukocyte protease inhibitor (SLPI) as a novel dedifferentiation biomarker in BRAFV600E-mutant PTC through integrated multi-omics analyses and functional validation. SLPI expression was significantly elevated in BRAFV600E-mutant tumors and correlated with advanced TNM stage, lymph node metastasis, and poor survival. Its overexpression was caused mechanistically by AP-1 transactivation and SLPI promoter hypomethylation. SLPI knockdown in PTC cells suppressed proliferation, increased anoikis sensitivity, and reduced FAK/AKT phosphorylation. Enrichment analysis linked high SLPI expression to PI3K/AKT pathway activation. Drug sensitivity prediction revealed that SLPI-high tumors were vulnerable to MAPK/AKT inhibitors. Notably, SLPI positively correlated with immune checkpoint genes, suggesting a potential immunosuppressive role. Our findings establish SLPI as a BRAFV600E-AP-1-FAK/AKT axis effector and propose its targeting as a strategy for PTC therapy.